High mobility group protein B1: a new biomarker of obesity in pregnant women?. (February 2015) - Giacobbe, A.; Grasso, R.; Imbesi, G.; Salpietro, C. D.; Grasso, L.; Laganà, A. S.; Triolo, O.; Di Benedetto, A.
Abstract Obesity is associated with an increased risk of an adverse pregnancy outcome. The aim of this study was to analyze the serum levels of high mobility group protein B1 (HMGB1) in obese pregnant women, to assess the role of this protein in the pathogenesis of this disease and to evaluate its possible function as a diagnostic marker for obesity-related complications in obese women. Study participants were randomly selected, from a cohort of pregnant women afferent to our department. A total of 120 women were enrolled in this study: 60 pregnant women had normal body mass index (BMI) and 60 women resulted obese. Pre-pregnancy BMI, weight increase and HMGB1 levels were evaluated for each pregnant woman enrolled. Matching serum HMGB1 levels in two groups, our data evidenced higher levels in the obese women, with a statistically significant difference (p = 0.0023). A significant positive univariate correlation was observed between serum HMGB1 levels and BMI in obese women. HMGB1 serum levels may therefore represent a predictive marker of disease in pregnant women (r = 20.9 and p = 0.0001). Further studies are needed in order to validate the role of this cytokine, with the aim of making it possible to use in clinical practice not only for diagnostic purposes, but especially for the early recognition of complications related to it.